2014
DOI: 10.4236/ajac.2014.53019
|View full text |Cite
|
Sign up to set email alerts
|

HS-SPME/GC-MS Analysis of VOC and Multivariate Techniques Applied to the Discrimination of Brazilian Varieties of Mango

Abstract: The present study analyzed the volatile compounds of three mango varieties (Tommy Atkins, Rosa and Espada) using the static headspace technique with SPME coupled to CG-MS. Multivariate methodologies, such as factorial design and response surface methodology, were used to optimize the conditions of adsorption and desorption of these substances. The data were evaluated by using principal components analysis (PCA) and hierarchical grouping analysis, in order to visualize grouping tendencies of volatile compounds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Fruit aroma components are affected by postharvest techniques, such as cold, heat, irradiation, atmospheric composition, and chemical applications . The volatile constituents and their concentrations in mango fruit peel and pulp have been studied in various cultivars in response to various postharvest conditions, such as heat vapor treatment, methyl jasmonate (MeJA) application, intact mango fruit compared to infested with fruit fly, various stages of fruit ripening, , and hot water dipping or fungicide treatments . Moreover, a reduction in aroma volatile production in “Kensington Pride” mango pulp was observed in response to CI .…”
Section: Introductionmentioning
confidence: 99%
“…Fruit aroma components are affected by postharvest techniques, such as cold, heat, irradiation, atmospheric composition, and chemical applications . The volatile constituents and their concentrations in mango fruit peel and pulp have been studied in various cultivars in response to various postharvest conditions, such as heat vapor treatment, methyl jasmonate (MeJA) application, intact mango fruit compared to infested with fruit fly, various stages of fruit ripening, , and hot water dipping or fungicide treatments . Moreover, a reduction in aroma volatile production in “Kensington Pride” mango pulp was observed in response to CI .…”
Section: Introductionmentioning
confidence: 99%
“…Benevides et al [32] determined the volatile compounds in three mango varieties (Tommy Atkins, Rosa and Espada) and found that the main classes of compounds were esters and terpenes. Among the identified compounds, only α-pinene, βmyrcene and caryophyllene were common to all three varieties.…”
Section: Mangomentioning
confidence: 99%